Evaluating the Road Damage of Flexible Pavement Using Digital Image - Angreni, Ida Ayu Ari; Adisasmita, Sakti Adji; Ramli, M. Isran; Hamid, Sumarni (International Journal of Integrated Engineering, 2018)
Project funding becomes the main problem in the evaluation of pavement conditions using mechanical tools. It is due to the price of these tools is quite expensive, added to that one type of tool only measures one particular condition. visual inspection method is a good solution to sort out the problems because it is quite practical, simple and efficient. However, there is a weakness in evaluating the damage of roads visually. The visual assessment method is highly subjective, depending on the assessor. Considering the weakness of the road damage assessment method visually, it is necessary to create an algorithm or a method in detecting and calculating the amount of the road damages quickly and precisely. This research offers the use of digital camera to detect the damages of the roads. The first step of the algorithm process is done by taking pictures using digital camera, so that it is resulting digital images to be processed. The result will give information about the types of road damages and the damage value of the road as well as monitoring the structural strength of the road material (core drill test) and the influence of traffic load on the damage road